HARMONI HINDU-MUSLIM DI BALI MELALUI KEARIFAN LOKAL: STUDI DI KABUPATEN JEMBRANA - saihu saihu (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
This paper discusses the process of creating harmony (ethical dialogue) between Hindus and Muslims through sarana ‘Urf (tradition) or local wisdom that is believed to have religious, philosophical, and sociological values as well as multicultural nuances for the Jembrana community of Bali Province. In his analysis, this paper uses the Integrative Communication Theory proposed by Kim Young Yun, focusing on the ‘Urf (tradition) which is used as a means to communicate and interact between the two religious communities, thus leading to the peaceful practice of Hindu society. and Muslims in Jembrana-Bali. Data sources were obtained through unstructured observations and interviews from March to July 2019 and using the case study method. The results of this study show that in order to create harmony in communication and interaction between Hindus and Muslims in Jembrana is through the traditions of Male, Ngejot, Rebana, and Mekepung. Harmonization built from the four traditions is the result of a deep sense of understanding about each other’s traditions and culture or intercultural transformation so as to grow a sense of brotherhood, understanding diversity, fostering community interest between the two religious communities, and can shape the character of Hindu and Muslim communities in Jembrana to be humanist, tolerant and inclusive, so that it leads to a process of association, integration, complementation and sublimation